Cardiotocography versus intermittent auscultation of fetal heart on admission to labour ward for assessment of fetal wellbeing - SMITH, VALERIE C; LALOR, JOAN (My University, 2012)
Background: The admission cardiotocograph (CTG) is a commonly used screening test consisting of a short (usually 20 minutes) recording of the fetal heart rate (FHR) and uterine activity performed on the mother?s admission to the labour ward. Objectives: To compare the effects of admission CTG with intermittent auscultation of the FHR on maternal and infant outcomes for pregnant women without risk factors on their admission to the labour ward. Search methods: We searched the Cochrane Pregnancy and Childbirth Group?s Trials Register (17 May 2011) (CENTRAL) (The Cochrane Library 2011 Issue 2 of 4), MEDLINE (1966 to 17 May 2011), CINAHL (1982 to 17 May 2011), Dissertation Abstracts (1980 to 17 May 2011) and the reference list of retrieved papers. Selection criteria: All randomised and quasi-randomised trials comparing admission CTG with intermittent auscultation of the FHR for pregnant women between 37 and 42 completed weeks of pregnancy and considered to be at low risk of intrapartum fetal hypoxia and of developing complications during labour. Main results We included four trials involving more than 13,000 women. All four studies included women in labour. Overall, the studies were at low risk of bias. Although not statistically significant using a strict P < 0.05 criterion, data are consistent with women allocated to admission CTG having, on average, a higher probability of an increase in incidence of caesarean section than women allocated to intermittent auscultation (risk ratio (RR) 1.20, 95% confidence interval (CI) 1.00 to 1.44, four trials, 11,338 women, T? = 0.00, I? = 0%). There were no differences between groups in other secondary outcome measures. Authors? conclusions: Contrary to continued use in some clinical areas, we found no evidence of benefit for the use of the admission cardiotocograph (CTG) for low-risk women on admission in labour. We found no evidence of benefit for the use of the admission CTG for low-risk women on admission in labour. Furthermore, the probability is that admission CTG increases the caesarean section rate by approximately 20%. The data lacked power to detect possible important differences in perinatal mortality. However, it is unlikely that any trial, or meta-analysis, will be adequately powered to detect such differences. The findings of this review support recommendations that the admission CTG not be used for women who are low risk on admission in labour. Women should be informed that admission CTG is likely associated with an increase in the incidence of caesarean section without evidence of benefit.
PUBLISHED
Systematic Review PubMed ID: 22336808
Keywords: cardiotocograph; CTG; cardiotocography; pregnancy